Eco-friendly biopolymer integrated three-dimensional hierachichal graphene materials for adsorptive removal of dyes and heavy metals - Lai, Kar Chiew (2021)
The discharge of effluent containing heavy metals and dyes from various industries has led to severe water pollution threatening all forms of life and the environment. Adsorption of these pollutants onto graphene oxide (GO) nanosorbent has potrayed promising results, however, its application in industrial wastewater remediation is restricted by its nano-sized dimension, making the recovery steps costly. Lately, three-dimensional (3D) graphene materials have attracted great attention as an effective adsorbent for wastewater treatment. The intrinsic properties of 3D graphene structure such as ultra large surface area and interconnected porous structure, can facilitate the transport of pollutants into the 3D network and provide abundant active sites for binding the pollutants.